2018
DOI: 10.1620/tjem.244.263
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-35 as a New Biomarker of Renal Involvement in Lupus Nephritis Patients

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease with a wide range of clinical presentations. Lupus nephritis (LN) is the most serious manifestation of SLE. , a member of the interleukin-12 family, has been identified as a novel anti-inflammatory cytokine. In the past ten years, the role of IL-35 in inflammatory and autoimmune diseases has been studied extensively. Serum IL-35 levels, however, have not been studied in LN patients. The aim of the study was to determine serum IL-35 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In the present study, the prevalence of renal disorder in SLE patients was 37.6% with median disease duration of 4.06 years. Previous study has suggested that serum IL-35 could be served as a potential biomarker of renal involvement in SLE patients; the serum levels of IL-35 were significantly lower in nephritis patients with higher levels of serum creatinine, blood urea nitrogen and blood uric acid [51]. Our result adds novel evidence in elucidating the genetic underpinnings driving nephritis among SLE patients.…”
Section: Discussionsupporting
confidence: 55%
“…In the present study, the prevalence of renal disorder in SLE patients was 37.6% with median disease duration of 4.06 years. Previous study has suggested that serum IL-35 could be served as a potential biomarker of renal involvement in SLE patients; the serum levels of IL-35 were significantly lower in nephritis patients with higher levels of serum creatinine, blood urea nitrogen and blood uric acid [51]. Our result adds novel evidence in elucidating the genetic underpinnings driving nephritis among SLE patients.…”
Section: Discussionsupporting
confidence: 55%
“…Interleukin‐35 (IL‐35), as a new member of the IL‐12 family , plays a key role in certain autoimmune diseases, including diabetes , antiphospholipid syndrome , systemic lupus erythematosus , and immune thrombocytopenia . IL‐35‐producing B cells were identified as pivotal players in the negative regulation of immunity as well, including the inhibition of macrophages and inflammatory T cells .…”
Section: Introductionmentioning
confidence: 99%
“…However, IL-35 [32] and TGF- β [31, 33] also play key roles in the pathogenesis of SLE. Study [34] found serum IL-35 levels were lower in active SLE compared to inactive disease and inversely correlated with SLEDAI-2K [34]. Furthermore, serum IL-35 levels were lower in patients with LN compared to SLE patients without LN [34].…”
Section: Bregs Participate In Human Sle Through Il-10 Il-35 or Tmentioning
confidence: 99%
“…Study [34] found serum IL-35 levels were lower in active SLE compared to inactive disease and inversely correlated with SLEDAI-2K [34]. Furthermore, serum IL-35 levels were lower in patients with LN compared to SLE patients without LN [34]. Serum IL-35 levels were found decreased in patients with SLE [35] and negatively correlated with the disease activity index.…”
Section: Bregs Participate In Human Sle Through Il-10 Il-35 or Tmentioning
confidence: 99%